Optimalisasi Teknologi Tepat Guna pada Budidaya Tanaman Bawang Merah dan Manajemen Usaha Bawang Goreng di Desa Mrangon Lawang dan Watuwungkuk, Kecamatan Dringu, Kabupaten Probolinggo, Jawa Timur - Elsye Tandelilin; Johny Rusdiyanto; Muhammad Aan Auliq (Jurnal ABM Mengabdi, 2017)
Community Service Activities is done by providing appropriate technology and business management to the community in Probolinggot. Activities focus on efforts to improve both quantitative and qualitative yields on shallot crops with the target group of onion farmers and improvement in business management with target groups woman entrepreneurs in the district of Dringu, Probolinggo. Implementation of activities for onion cultivation is done by giving appropriate technology onion plants with the improvement of fertilizer composition and maintenance during the planting period. As for business management activities are treated by providing training and guidance of brand making and packaging directly to the moms of fried onion entrepreneurs as well as the provision of tools such as spinner aids and the real activity of dedication to the community is apparently with appropriate technology given can increase the yield about 30 - 40%. The woman entrepreneurs fried onions agree using certain brand names and packaging improvements are increasingly diverse. In its implementation found many obstacles, especially in changing the mindset of the target group and the difficulty of making agreements in the group. Finally formed a group of mothers fried onion entrepreneurs berdaqsarkan agreement together. Generally, positive results such as improved crops and fried onion marketing can be offered at higher prices because the fried onion products are more crunchy and can be sold at relatively high prices, so the value of profit is seen to increase. It is expected that the results of this activity will be a reference for onion farmer groups and mothers of fried onion entrepreneurs to be able to increase productivity and bring the good name of subdistrict Watuwungkuk in the future.